In medio stat virtus: The importance of studying mediums in hypnosis research. Issue 1 (15th October 2021) - Perri, Rinaldo Livio
ABSTRACT: Most of the experimental investigations on hypnosis used to compare small samples of individuals with low or high responsiveness to hypnosis by systematically excluding medium responders. The present article underlines the limitations of this methodological approach that may have partially weakened the scientific impact of hypnosis research. In fact, the mediums-neglecting bias might be one of the reasons why some investigations suffer from low replicability and generalizability. Themes such as hypnotizability scales, suggestibility, statistical power, and research design are critically reviewed with the aim of proposing a more rigorous approach that boost up impact and reliability of hypnosis research. In particular, the recruitment of medium hypnotizables and the adoption of a within-instead of a between-subjects design currently seem to be some of the best recommendations for strengthening hypnosis research, as well as to renew the dialogue between clinical and experimental hypnosis.